Musical monuments of Hungarian history: Ferenc Erkel’s pre-revolution operas - Robinson, BJ (2019)
A rapidly shifting social and political climate characterised the period between the 1825 Hungarian Diet and the revolution of 1848. An inherited fear of nemzethalál, ‘nation death’, drove attempts to fight the spectre of obscurity through language cultivation, social-political reform, nation-building projects, and representing history artistically. Exemplified by the national theatre project, opera became embroiled in discourse surrounding the educative potential of Hungarian-language artforms. Anxieties stemming partially from imperialism shaped a cyclic understanding of a sinful past, punished present and uncertain future. Erkel’s Bátori Mária which inaugurated the Nemzeti Színház, ‘National Theatre’, encapsulates an ambiguous representation of Hungary’s history. Abortive attempts to disrupt a series of calamities only reinforced the understanding of Árpád history as a cycle of trespasses with repercussions reverberating into the nineteenth century. As the 1840s progressed, the revolutionaries anticipated a rupture with the past. During the revolutionary year, the theatre staged a programme comprising musical-theatrical pieces embodying overt revolutionary messages. Numbers from Erkel’s second opera Hunyadi László, a work littered with anti-Habsburg textual and musical references, featured prominently in this repertoire. This study challenges traditional understandings of how Hunyadi László relates to revolutionary rhetoric, illuminating how the tropes of defeat, victimhood, sacrifice and resurrection are in tension in this medieval narrative. Erkel’s operas composed in the pre-revolution decade illuminate how historical interpretation related to fears surrounding legacy. Operatic models familiar to the Pest-Buda audiences became vessels for presenting versions of history beholden to contemporary understandings of the past in relation to the future. The contrast between Bátori Mária and Hunyadi László not only reflects the rapid momentum radical ideologies gathered approaching 1848, but how historical interpretation shifted through political and artistic polemics. This study illuminates how anxieties relating to identity interpolate with presenting history on the stage in Erkel’s pre-revolution operas.